2021
DOI: 10.1109/access.2021.3053116
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain Scattering Characteristics and Jamming Effectiveness in Corner Reflectors

Abstract: The outboard corner reflectors are widely used as a countermeasure to radar tracking and detection. Therefore, it is essential to determine the composite time-domain scattering characteristics of the corner reflector and ship against the sea background and the jamming effectiveness of the corner reflector array. In this paper, the composite electromagnetic scattering characteristics of ship target, corner reflector, and the sea surface are studied based on the time-domain bouncing ray method (TDSBR). The radar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This property results in the corner reflector exhibiting a pronounced backward radar cross−section and the generation of a robust jamming signal [3]. Proper assignment of multiple corner reflectors can simulate false targets similar to ships, which will substantially enhance the interference effect [4][5][6]. Consequently, the array of corner reflectors has attracted greater interest [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This property results in the corner reflector exhibiting a pronounced backward radar cross−section and the generation of a robust jamming signal [3]. Proper assignment of multiple corner reflectors can simulate false targets similar to ships, which will substantially enhance the interference effect [4][5][6]. Consequently, the array of corner reflectors has attracted greater interest [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This theory was employed to establish the statistical model of Radar Cross Section (RCS) of the OR array, and this work found that the OR array has better omnidirectivity than single OR. Luo simulated the RCS of ORs with different geometric features through the Shooting and Bouncing Ray (SBR) [8] method, and the regular of its RCS versus angles and radius was summarised. Nevertheless, the above achievements are all based on the static condition, and there is still no research or report with regard to the dynamic properties of ACR.…”
Section: Introductionmentioning
confidence: 99%
“…Passive jamming uses angular reflectors and other devices to change the scattering mode of electromagnetic waves, demonstrating the qualities of cost-effectiveness and rapid response [10,11]. However, traditional passive devices possess a singular and fixed electromagnetic property after undergoing processing.…”
Section: Introductionmentioning
confidence: 99%